JAK3/STAT5/6 Pathway Alterations Are Associated with Immune Deviation in CD8+ T Cells in Renal Cell Carcinoma Patients. (22nd March 2010) - Cavalcanti, Elisabetta; Gigante, Margherita; Mancini, Vito; Battaglia, Michele; Ditonno, Pasquale; Capobianco, Carmela; Cincione, Raffaele I.; Selvaggi, Francesco P.; Herr, Wolfgang; Storkus, Walter J.; Gesualdo, Loreto; Ranieri, Elena
Abstract : To investigate the molecular mechanisms underlying altered T cell response in renal cell carcinoma (RCC) patients, we compared autologous and allogeneic CD 8 + T cell responses against RCC line from RCC patients and their HLA-matched donors, using mixed lymphocyte/tumor cell cultures (MLTCs). In addition, we analyzed the expression of molecules associated with cell cycle regulation. Autologous MLTC responder CD 8 + T cells showed cytotoxic activity against RCC cell lines; however the analysis of the distribution of CD 8 + T-cell subsets revealed that allogenic counterparts mediate superior antitumor efficacy. In RCC patients, a decreased proliferative response to tumor, associated with defects in JAK3/STAT5/6 expression that led to increased p27KIP1 expression and alterations in the cell cycle, was observed. These data define a molecular pathway involved in cell cycle regulation that is associated with the dysfunction of tumor-specific CD 8 + effector cells. If validated, this may define a therapeutic target in the setting of patients with RCC.